2003
DOI: 10.1194/jlr.m200339-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

HDL regulates the displacement of hepatic lipase from cell surface proteoglycans and the hydrolysis of VLDL triacylglycerol

Abstract: We have previously shown that hepatic lipase (HL) is inactive when bound to purified heparan sulfate proteoglycans and can be liberated by HDL and apolipoprotein A-I (apoA-I), but not by LDL or VLDL. In this study, we show that HDL is also able to displace HL directly from the surface of the hepatoma cell line, HepG2, and Chinese hamster ovary cells stably overexpressing human HL. ApoA-I is more efficient at displacing cell surface HL than is HDL, and different HDL classes vary in their ability to displace HL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 34 publications
9
37
0
Order By: Relevance
“…Lipidation of these apolipoproteins with POPC and TG has a similar effect on denaturation curves and substantially decreases the ability of GdnHCl to unfold the ␣ -helical structure of apoA-I and apoA-II. These data are similar to what has been observed previously in thermal denaturation studies (2,38,35). Table 2 a LpA-I complexes were prepared by cosonication as described.…”
Section: Effect Of Apoa-ii On the Size And Charge Of The Lpa-i Complexessupporting
confidence: 80%
See 1 more Smart Citation
“…Lipidation of these apolipoproteins with POPC and TG has a similar effect on denaturation curves and substantially decreases the ability of GdnHCl to unfold the ␣ -helical structure of apoA-I and apoA-II. These data are similar to what has been observed previously in thermal denaturation studies (2,38,35). Table 2 a LpA-I complexes were prepared by cosonication as described.…”
Section: Effect Of Apoa-ii On the Size And Charge Of The Lpa-i Complexessupporting
confidence: 80%
“…VLDL hydrolysis by HL was characterized in the presence or absence of HDL or reconstituted HDL complexes as previously described (35). Briefly, each sample contained the lipoprotein substrate (350 M VLDL), purified HL (26 U), 75 l of incubation buffer (0.33 M Tris-HCl, pH 8.3, 1% fatty acid free-BSA, and 5 mM CaCl 2 ), PBS (to a final volume of 250 l), and increasing concentrations of HDL or LpA-I/A-II complexes as indicated in Fig.…”
Section: Purification and Assay Of Hepatic Lipasementioning
confidence: 99%
“…Therefore, the enzyme may not be inactive, but catalytic activity could be masked because of association with some plasma component. Very recently (34), it was reported that hepatic lipase activity is inhibited by association with several HDL fractions or pure apoA-I. Note that we found that hepatic lipase is assiciated with HDL in rat plasma.…”
Section: Inactive Hepatic Lipase In Rat (Nonheparin) Plasmasupporting
confidence: 60%
“…Furthermore, this release from the liver may not be spontaneous. HDL displaces hepatic lipase from the cell surface in both HepG2 cells and CHO cells expressing human hepatic lipase (34). HDL may thus also release hepatic lipase from binding sites in liver into the bloodstream.…”
Section: Inactive Hepatic Lipase In Rat (Nonheparin) Plasmamentioning
confidence: 99%
“…Factors that regulate the dissociation of HL from cell surfaces in vivo are unclear. We have recently observed that apoA-I and HDL can displace hHL from purified proteoglycans in vitro and from cultured cell surfaces (36,37) and that hHL is active only when it is free in solution. The present study with the HSPG binding-deficient hHLmt provides in vivo evidence that the catabolism of HDL may occur in the circulation by the blood-borne HL, whereas the cell surfacebound hHL is less involved.…”
Section: Discussionmentioning
confidence: 99%